2012
DOI: 10.1016/j.giq.2011.09.010
|View full text |Cite
|
Sign up to set email alerts
|

The small group subtlety of using ICT for participatory governance: A South African experience

Abstract: The greater number of government efforts to stimulate participative governance in communities using Information and Communication Technology (ICT) often fall short of expectations. In South Africa extending e-government to communities has been in the form of more and/or better equipped ICT-enabled community centres, called Thusong Service C e n t r e s . I n t h i s p a p e r , b a s e d o n a c t i o n r e s e a r c h e x p e r i e n c e s , w e r e p o r t o u t c o m e s o f interpretive research into ICT-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 12 publications
0
17
0
1
Order By: Relevance
“…Siguiendo esta l铆nea (Janssen y Voort, 2016a;Sivarajah et al, 2015;Twinomurinzi et al, 2012), explican que los cambios en el medio ambiente, las expectativas de la econom铆a global y los desarrollos tecnol贸gicos como grandes almacenes datos, an谩lisis de datos, apertura de datos vinculados y web sem谩ntica influyen en los valores sociales, requiriendo la adaptaci贸n de mayores niveles de privacidad y ciberseguridad. La gobernanza es necesaria para tomar las decisiones necesarias y responder a estos acontecimientos, lo que plantea nuevas exigencias, requiriendo la adopci贸n y cambio de pol铆ticas, legislaciones, sistemas e incluso estructuras internas para tratar con ellos.…”
Section: Gobierno Corporativo Y Gobierno De Tiunclassified
“…Siguiendo esta l铆nea (Janssen y Voort, 2016a;Sivarajah et al, 2015;Twinomurinzi et al, 2012), explican que los cambios en el medio ambiente, las expectativas de la econom铆a global y los desarrollos tecnol贸gicos como grandes almacenes datos, an谩lisis de datos, apertura de datos vinculados y web sem谩ntica influyen en los valores sociales, requiriendo la adaptaci贸n de mayores niveles de privacidad y ciberseguridad. La gobernanza es necesaria para tomar las decisiones necesarias y responder a estos acontecimientos, lo que plantea nuevas exigencias, requiriendo la adopci贸n y cambio de pol铆ticas, legislaciones, sistemas e incluso estructuras internas para tratar con ellos.…”
Section: Gobierno Corporativo Y Gobierno De Tiunclassified
“…A few researches have done for emerging countries, most of them are case studies where building and implementing e-government projects has no a common star up or road map. A recent study by the United Nations has shown that many emerging economies are making positive strides to develop their e-government capabilities [6], e-government adoption in Latin America [7], e-government development in the Caribbean, participatory governance in South Africa [8], and e-government project in Iran [9], are especial cases for egovernment initiatives, and each of these articles contributes to the understanding of e-government by focusing on particular issues related to e-government in specific parts of the world. After we cross academic research works, we come to conclude that there is no discussion of how emerging countries could implement their e-government system base on circumstance of its current state of development.…”
Section: Literature Overviewmentioning
confidence: 99%
“…A few researches have done for emerging countries, most of them are case studies where building and implementing e-government projects has no a common star up or road map. A recent study by the United Nations has shown that many emerging economies are making positive strides to develop their egovernment capabilities [6], e-government adoption in Latin America [7], e-government development in the Caribbean (Joseph and Jeffers, 2009), participatory governance in South Africa [8], and e-government project in Iran [9], are especial cases for e-government initiatives, and each of these articles contributes to the understanding of e-government by focusing on particular issues related to e-government in specific parts of the world. After we cross academic research works, we come to conclude that there is no discussion of how emerging countries could implement their e-government system base on circumstance of its current state of development.…”
Section: Literature Overviewmentioning
confidence: 99%